From castle to teahouse : Japanese architecture of the Momoyama period - Kirby, John, Jr (Charles E. Tuttle Company, 1962)
The Momoyama period of Japanese art history, at the turn of the 16th century, is perhaps best known to the West through the resplendent paintings of the Kano masters and their fellow artists. Yet this same period offers such a variety of architectural pleasures that, in at least one of its many facets, it makes an appeal to every taste. It ranges from the largest and most imposing castles to the smallest and most tastefully designed teahouses. Paintings and gardens are an integral part of it, as they are in all Japanese architecture, and here, also, the range extends from the gorgeous and.